A new species of Dudgeodes Sartori, 2008 (Ephemeroptera: Teloganodidae) from Thailand - Martynov, Alexander V.; Palatov, Dmitry M.; Boonsoong, Boonsatien (Zootaxa, 2016)
A new species of the genus Dudgeodes Sartori, 2008 is described from Thailand. It is the first representative of the genus reported from this country. The species is described based on mature nymphs. Dudgeodes romani sp. nov. differs from other species of the genus by the length of antennae; coloration of male eyes; shape of abdominal median tubercles; features of the tarsal claws, forefemora, gills and segments of the labial palps, and by chaetotaxy.